2010
DOI: 10.1504/ijbsr.2010.035077
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the successful exploitation of ERP systems in Chinese state-owned enterprises

Abstract: Adopting a systems perspective, the research presented in this paper aims at identifying, assessing and discussing potential cultural, organisational and system barriers to the successful exploitation of Enterprise Resource Planning (ERP) systems in the context of Chinese State Owned Enterprises (SOE). The study adopted a deductive research design by using a cross-sectional questionnaire survey. The questionnaire design was based on a theoretical ontology of barriers drawn from a systematic literature review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Other typical causes contain uninvolving affected employees in planning and developing stages, insufficient training for the users, and data conversion and testing failures [4]. Furthermore, reference [9] identified organizational barriers, such as inefficient collaboration and communication between functional department, short-term behavior of top managers, low user involvement, low-skilled and ill-trained users are main triggers of the occurrence of other ERP post-implementation risks in China. This paper aimed to test the understanding of managers and users on ERP system in postimplementation stage in a typical SOE group, moreover, the main organizational barriers are explored.…”
Section: II Literature Reviewmentioning
confidence: 99%
“…Other typical causes contain uninvolving affected employees in planning and developing stages, insufficient training for the users, and data conversion and testing failures [4]. Furthermore, reference [9] identified organizational barriers, such as inefficient collaboration and communication between functional department, short-term behavior of top managers, low user involvement, low-skilled and ill-trained users are main triggers of the occurrence of other ERP post-implementation risks in China. This paper aimed to test the understanding of managers and users on ERP system in postimplementation stage in a typical SOE group, moreover, the main organizational barriers are explored.…”
Section: II Literature Reviewmentioning
confidence: 99%
“…The discrepancy between the Western and Chinese culture has been reported to have profound impact on ERP innovation [7,10,13]. In particular, data format and language are identified as typical cultural issues influencing the adoption and usage of Western ERP packages in the Chinese context [17,7,18].…”
Section: Cultural Impact On Erp Exploitationmentioning
confidence: 99%
“…According to Hofstede's study [20], the Chinese culture is characterized by high power distance, high collectivism, low uncertainty avoidance, and long-term orientation. An extensive review of the IS literature [8,13,21,22,23] suggested that Hofstede's dimensions of power distance, uncertainty avoidance and collectivism often have essential effects on IS adoption and usage in Chinese companies. These three Hofstede dimensions were thus selected to be explored intensively in this ERP study.…”
Section: Cultural Impact On Erp Exploitationmentioning
confidence: 99%
See 2 more Smart Citations